Reduced intensity allogeneic stem cell transplantation for follicular lymphoma relapsing after an autologous transplant achieves durable long-term disease control: an analysis from the Lymphoma Working Party of the EBMT†. (8th March 2016) - Robinson, S. P.; Boumendil, A.; Finel, H.; Schouten, H.; Ehninger, G.; Maertens, J.; Crawley, C.; Rambaldi, A.; Russell, N.; Anders, W.; Blaise, D.; Yakoub-Agha, I.; et al.
Abstract : A substantial fraction of patients with FL will relapse after an autoSCT and therapy for such patients remains challenging. There is currently no published study analysing the outcome of RICalloSCT exclusively in this setting. We report the outcomes for a large cohort of patients and describe how a RICalloSCT may achieve very impressive disease control albeit at the cost of significant toxicity. Abstract: Background: Patients with follicular lymphoma (FL) relapsing after an autologous transplant (autoSCT) may be treated with a variety of therapies, including a reduced intensity allogeneic transplant (RICalloSCT). We conducted a retrospective analysis of a large cohort of patients undergoing RICalloSCT for FL in this setting. Patients and methods: A total of 183 patients, median age 45 years (range 21–69), had undergone an autoSCT at a median of 30 months before the RICalloSCT. Before the RICalloSCT, they had received a median of four lines (range 3–10) of therapy and 81% of patients had chemosensitive disease and 16% had chemoresistant disease. Grafts were donated from sibling (47%) or unrelated donors (53%). Results: With a median follow-up of 59 months, the non-relapse mortality (NRM) was 27% at 2 years. The median remission duration post-autoSCT and RICalloSCT was 14 and 43 months, respectively. The 5-year relapse/progression rate, progression-free survival and overall survival were 16%, 48% and 51%, respectively, and were associated with age and disease status at RICalloSCT. Conclusion: These data suggest that an RICalloSCT is an effective salvage strategy in patients with FL recurring after a prior autoSCT and might overcome the poor prognostic impact of early relapse after autoSCT.